2018
DOI: 10.1016/j.tetlet.2018.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Repetition of chemistry from a recently retracted paper. A cautionary note

Abstract: The base-catalyzed condensation reaction between (E)-4-phenylbut-2-enal and phenylpropargyl aldehyde recently reported in the literature to provide formylcyclobutadiene was repeated under the published conditions. The product obtained was identified as (E)-5-phenyl-2-((E)-styryl)pent-2-en-4-ynal rather than the reported 2phenyl-3-styrylcyclobutadiene-1-carboxaldehyde. The structure assignment is supported by NMR and IR data and a x-ray structure of the crystalline alcohol obtained by Luche reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The distribution generally reflects the number of papers published by each country. We see that 31.4% of retracted papers involve a Chinese affiliation, which is in line with the fact that 30 The ratio of retraction in China is of particular interest here, given the country's cash-per-publication reward policy 16 has been suspected to drive researchers toward, at best, the production of more papers of lower scientific significance, or at worst a negative impact on academic ethics. 17 The data show that this does not, for the field and period studied, lead to an increase in the ratio of retraction.…”
Section: ■ How Many Papers Are Retracted?supporting
confidence: 70%
See 2 more Smart Citations
“…The distribution generally reflects the number of papers published by each country. We see that 31.4% of retracted papers involve a Chinese affiliation, which is in line with the fact that 30 The ratio of retraction in China is of particular interest here, given the country's cash-per-publication reward policy 16 has been suspected to drive researchers toward, at best, the production of more papers of lower scientific significance, or at worst a negative impact on academic ethics. 17 The data show that this does not, for the field and period studied, lead to an increase in the ratio of retraction.…”
Section: ■ How Many Papers Are Retracted?supporting
confidence: 70%
“…Another interesting inquiry, related to a retracted paper, is the work of Ryan et al, who repeated the chemical reactions of a retracted organic chemistry paper (DOI: 10.1021/acs.orglett.7b02161) and provided a full analysis of the shortcomings in the analysis of the original paper. 30 Some retraction notices even acknowledge whistleblowers (when they did not wish to remain anonymous, we suppose!) "for the considerable ef fort put into collecting the evidence and reporting this case of multiple publication", which I see as an encouraging note.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 In the meantime, the original paper was retracted and our proposal was validated by X-ray analysis. 77 Knowing the most likely structure of a natural product in advance is of utmost importance for synthetic groups, allowing them to save time, money, and man-power by directing the experimental efforts toward the right candidate (in contrast to the still popular approach of preparing different isomers). In collaboration with the group of Ronaldo Pilli (UNICAMP, Brazil), we have explored this "computer-guided total synthesis of natural products" idea, 78 which to date has led to the synthesis and stereochemical revision or validation of three natural products (Figure 10).…”
Section: ■ In Silico Revision Of Natural Productsmentioning
confidence: 99%
“…Soon after the paper was published, we demonstrated that this rare structure was highly unlikely, suggesting a more logical deconjugated aldol condensation product as the actual structure . In the meantime, the original paper was retracted and our proposal was validated by X-ray analysis …”
Section: In Silico Revision Of Natural Productsmentioning
confidence: 99%